Effects of neighbor familiarity on reproductive success in the great tit (Parus major) - Grabowska-Zhang, A; Wilkin, T; Sheldon, B (2012)
Social interactions can often affect the fitness of individuals. Territorial animals frequently interact with their neighbors, and long-term familiarity might lead to the development of cooperative relationships, which might influence the fitness of neighboring individuals. Here we test the hypothesis that familiarity with neighbors positively affects reproductive success in the great tit (Parus major). We used data from a 41 year long-term study of the great tit to quantify neighbor familiarity and its relationship with different stages in the great tit reproductive cycle. Breeding birds had from 0 to 11 neighbors with whom they were familiar by sharing a territory boundary the year before; although owing to low annual survival, the mean proportion of familiar neighbors (0.1) was quite small. Despite the low average proportion of familiar neighbors, we found evidence suggesting positive effects of increased familiarity: females with more familiar individuals in their neighborhood laid larger clutches. We also found that both males and females with more familiar neighbors had a greater chance of successfully fledging offspring. These results suggest that long-term familiarity can benefit territorial breeding birds. Future work is needed to address the underlying mechanisms of how neighbor familiarity influences individual fitness. © The Author 2011.